SOCIOCULTURAL SAFETY CONCEPT IN EDUCATIONAL ENVIRONMENT OF UNIVERCITY - Maksim Sokolovskii (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the structure of the concept of sociocultural safety (SCS) of the educational environment of university, examines approaches to its assessment from the standpoint of the current state of the pedagogical and psychological sciences. The main components of the SCS are presented and described: preservation and development of culture; human development as understood by the UN; resilience, understood both in a narrow sense (as a subjectivity) and broadly, as a set of personal and social factors that enable a person to overcome life's difficulties, recover and move towards the achievement oftraditional personal values; competent actions of the authorities and representatives of ethno cultures themselves, which is consistent with local and global trends in the formation and preservation of cultures of ethnic groups.